2015
DOI: 10.1634/theoncologist.2014-0285
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoking Status on the Progression-Free Survival of Non-Small Cell Lung Cancer Patients Harboring Activating Epidermal Growth Factor Receptor (EGFR) Mutations Receiving First-Line EGFR Tyrosine Kinase Inhibitor Versus Platinum Doublet Chemotherapy: A Meta-Analysis of Prospective Randomized Trials

Abstract: Background. Univariate analyses from several randomized phase III trials seemed to suggest ever-smokers with advanced mutated epidermal growth factor receptor (EGFRm) non-small cell lung cancer (NSCLC) did not seem to benefit from EGFR tyrosine kinase inhibitors (TKIs) as first-line treatment when compared with platinum-doublet chemotherapy as measured by progression-free survival (PFS). Methods. A literature-based meta-analysis of PFS outcomes as measured by log-transformed pooled hazard ratio (HR) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 27 publications
7
40
0
Order By: Relevance
“…Previous studies have reported that patients with NSCLC harboring EGFR mutations and a positive smoking history showed a relatively low response rate, or short PFS, to EGFR-TKI therapy [21,22,23,24,25,26]. While our study was restricted to patients who received only gefitinib as EGFR-TKI therapy, in the aforementioned previous studies [9,10,11,12], EGFR-TKI therapy involved erlotinib, gefitinib or afatinib.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that patients with NSCLC harboring EGFR mutations and a positive smoking history showed a relatively low response rate, or short PFS, to EGFR-TKI therapy [21,22,23,24,25,26]. While our study was restricted to patients who received only gefitinib as EGFR-TKI therapy, in the aforementioned previous studies [9,10,11,12], EGFR-TKI therapy involved erlotinib, gefitinib or afatinib.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that patients with NSCLC harboring activating EGFR mutations and a positive smoking history exhibit a relatively low response rate to EGFR-TKI therapy (or short PFS) [25-30]. A meta-analysis of 9 studies showed that after TKI treatment, PFS of nonsmokers was longer than in ever smokers among advanced NSCLC patients with an EGFR mutation [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, EGFR mutation status had no significant effect on the clinical outcome. Also, recent metaanalyses (17,30) showed that non-smokers are likely to have a longer PFS than smokers when undergoing EGFR-TKI therapy for diagnosed EGFR-mutant NSCLC. A recent study by Mitchell et al (16) concluded that controversies in the survival outcomes of smokers versus non-smokers after EGFR-TKI therapy may be due to incomplete data on smoking history, and that its relationship with treatment response has not been comprehensively analyzed.…”
Section: Discussionmentioning
confidence: 99%